Many roads lead to Rome--is that true of the teaching and learning of pharmacology? Lessons from three medical schools in Malaysia - Sim, Si Mui; Achike, Francis I.; Geh, S.L. (Malaysian Medical Association, 2005)
In Malaysia many new medical schools (both public and private) have been set up in the last 12 years. As a result of global changes and local adjustments made in medical training, cross-breeds of different medical curricula have produced a wide spectrum of teaching-learning methods in these medical schools. In this paper, we have selected three medical schools--two public (Universiti Malaya and Universiti Putra Malaysia) and one private (International Medical University) to illustrate different approaches in the teaching-learning of pharmacology that exist in Malaysia. How do these different teaching-learning approaches affect the students' interest and ability to "master" pharmacology and in turn to develop a good prescribing practice?